Investor reaction to strategic emphasis on earnings numbers: An empirical study - Sadique, Shibley; Rahman, M. (Vizja Press & IT, 2013)
We analyze the earnings information and stock prices of S&P500 firms and find that investors followingS&P500 stocks (i) respond more to pro forma earnings than to GAAP earnings, (ii) respond toan emphasis on pro forma earnings, and (iii) are fixated on pro forma earnings. We provide the firstdirect evidence that a strategic emphasis on earnings numbers may affect return volatility. Further,our results do not support the argument that a larger investor response to Street earnings might bedriven by large differences between the Street numbers and GAAP numbers.